2010
DOI: 10.1007/bf03379577
|View full text |Cite
|
Sign up to set email alerts
|

Consciousness: A Computational Paradigm Update

Abstract: This dualist model of mind-body addresses the formal and physical limits to computation that critics of artificial intelligence argue are the reason computers will never produce really intelligent machines. This model describes potential ideal computational leverage mechanisms that are based upon primitive properties of the universe (such as space, time, and number of dimensions) derived from modern physics consistency arguments. An intuitive model of computational costs is introduced to create a framework for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It is suggested that qualia, raw sensory and emotional subjective feelings arise secondary to having evolved into a higher order of thought system, and that sensory and emotional processing feels like something because it would be unparsimonious for it to enter the planning and higher order thought system and not feel like something (Matzke, 2010[160]). Raw sensory feels and subjective states associated with emotional and motivational states, may not necessarily arise first in evolution (Rolls, 2007[196]).…”
Section: Miscellaneous Facets and Approaches To The Study Of Conscmentioning
confidence: 99%
“…It is suggested that qualia, raw sensory and emotional subjective feelings arise secondary to having evolved into a higher order of thought system, and that sensory and emotional processing feels like something because it would be unparsimonious for it to enter the planning and higher order thought system and not feel like something (Matzke, 2010[160]). Raw sensory feels and subjective states associated with emotional and motivational states, may not necessarily arise first in evolution (Rolls, 2007[196]).…”
Section: Miscellaneous Facets and Approaches To The Study Of Conscmentioning
confidence: 99%